Current and emerging surveillance strategies to expand the window of opportunity for curative treatment after surgery in colorectal cancer. Issue 4 (April 2013) - Lin Koo, Si; Wen, Jin Hang; Hillmer, Axel; Cheah, Peh Yean; Tan, Patrick; Tan, Iain Beehuat
Colorectal cancer is the third most common cancer globally. At diagnosis, more than 70% of patients have nonmetastatic disease. Cure rates for early-stage colorectal cancer have improved with primary screening, improvements in surgical techniques and advances in adjuvant chemotherapy. Despite optimal primary treatment, 30–50% of these patients will still relapse. While death will result from widespread metastatic disease, patients with small volume oligometastatic disease are still considered curable with aggressive multimodality therapy. Hence, early detection of relapsed cancer when it is still amenable to resection expands the window of opportunity for cure. Here, the authors review the modalities currently employed in clinical practice and the evidence supporting intensive surveillance strategies. The authors also discuss ongoing clinical trials examining specific surveillance programs and emerging modalities that may be deployed in the future for early detection of metastatic disease.